2016
DOI: 10.1038/srep37715
|View full text |Cite
|
Sign up to set email alerts
|

The minimum area requirements (MAR) for giant panda: an empirical study

Abstract: Habitat fragmentation can reduce population viability, especially for area-sensitive species. The Minimum Area Requirements (MAR) of a population is the area required for the population’s long-term persistence. In this study, the response of occupancy probability of giant pandas against habitat patch size was studied in five of the six mountain ranges inhabited by giant panda, which cover over 78% of the global distribution of giant panda habitat. The probability of giant panda occurrence was positively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 87 publications
0
34
0
Order By: Relevance
“…A ROC illustrates the diagnostic ability of a binary classifier system as its discrimination threshold is varied. ROC analyses has been used in medicine (Levy et al 2006), radiology (Obuchowski 2003), biometrics (Toh et al 2008), model performance assessment (Qing et al 2016), and other areas for many decades. The area under the ROC curve (AUC) is a measure of how well a parameter can distinguish between two diagnostic groups (diseased/normal).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A ROC illustrates the diagnostic ability of a binary classifier system as its discrimination threshold is varied. ROC analyses has been used in medicine (Levy et al 2006), radiology (Obuchowski 2003), biometrics (Toh et al 2008), model performance assessment (Qing et al 2016), and other areas for many decades. The area under the ROC curve (AUC) is a measure of how well a parameter can distinguish between two diagnostic groups (diseased/normal).…”
Section: Discussionmentioning
confidence: 99%
“…The study area is located in the LNNR (Fig. 1) (Qing et al 2016). The releasing enclosure, where the soft release projects were implemented, is located in the natural forest in the LNNR reserve.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Xiaoxiangling Mountains contained the most fragmented habitats, and the giant panda populations were the smallest and most threatened within the species' range (Qing et al 2016). Liziping is currently the primary site of giant panda translocations and releases into the wild; several individuals have been released in the reserve since 2009 (Yang et al 2018).…”
Section: Study Areamentioning
confidence: 99%
“…Even though studies have shown that the size of the home range, activity range, and activity patterns of translocated giant panda individuals are similar to wild giant pandas (Gu et al 2011, Yang et al 2018, because of natal habitat preferences and unfamiliarity with the new environment, the movement and spread of translocated giant pandas may be affected. Habitat fragmentation is the most important threat to the sustainable survival of the giant panda (Pan 1995, Qing 2016. The wild giant panda is distributed in twenty-four habitat patches along six mountain ranges in western China (State Forestry Administration 2015, Swaisgood et al 2018).…”
Section: Introductionmentioning
confidence: 99%